Disability and youth sport [ - Fitzgerald, Hayley (International studies in physical education and youth sport, 2009)
"How can, or does, youth sport reconcile what seems to be a fundamental contradiction between understandings of sport and disability?" "Has youth sport been challenged in any way?" "Have alternative views of sport for disabled people been presented?" "Examining some of the latest research, this book considers the relationship between sport and disability by exploring a range of queslions suchas these." "Disability and Youth Sport challenges current thinking and serves to stimulate progressive debate in this area. Drawing on a breadth of literature from sports pedagogy, sociology of sport, disability studies, inclusive education and adopted physical activity, a socially critical dialogue is developed where the voices of young disabled people are central." "With its comprehensive coverage and expert contributors from around the globe, this book is an ideal text for students at all levels with an interest in youth sport, disability studies or sport policy."--BOOK JACKET